Answer:
Since we're dealing with absolute value we'll have two answers.
a= c/x-b/x
a= -c/x-b/x
Explanation:
Since we can't combine any values inside the absolute value signs we get rid of the absolute value signs.
Now we have: ax+b=c
since we're trying to get a by itself, we subtract the b to get ax= c-b
Now we divide the x and since we can't directly put it with a single value on the right side, we have to put it with both the c and b. Now we have a=c/x-b/x.
For the second answer, you first put a negative with the c. ax+b= -c
Now you solve exactly the same way you did above.
Hope this helps! :)